One Year Outcomes From a Prospective Multicenter Investigation Device Trial of a Novel Conformal Mesh Interbody Fusion Device. Issue 2 (15th January 2021) - Driver, Joseph; Huang, Kevin T.; Krag, Martin; Bydon, Mohamad; Nunley, Pierce; Lavoie, Stephane; Lu, Yi; Stone, Marcus; Chi, John H.
Abstract : Study Design: A prospective multicenter investigational device exempt trial is underway evaluating a novel conformable mesh interbody fusion device in subjects undergoing single-level fusion for degenerative disc disease. Patients meeting inclusion and exclusion criteria were offered enrollment. There is no comparative group in this study. Objective: Establish the short and long-term safety and effectiveness of a novel conformable mesh interbody fusion device in subjects undergoing single-level fusion for degenerative disc disease unresponsive to conservative care. Summary of Background Data: Transforaminal lumbar interbody fusion remains a critical procedure for patients with degenerative lumbar disc disease. Increasingly minimally invasive techniques have been proposed to minimize muscle dissection and tissue damage with the goal of minimizing pain and length of stay. Methods: One hundred two subjects were enrolled across 10 sites. Ninety nine subjects remained available for follow-up at 12-months. Physical evaluations/imaging were performed serially through 12-months. Validated assessment tools included 100 mm visual analogue scale (VAS) for pain, Oswestry Disability Index (ODI) for function, and computerized tomography scan for fusion. Independent committees were used to identify adverse events and for assessment of radiographic fusion. Results: Reductions in low back pain (LBP)/leg pain and improvements in functional status occur early and are maintained through 12-month follow-up. Mean VAS-LBP change from baseline to 6-weeks post-op (–46 mm) continued to improve through 12 months (–51 mm). Similar trends were observed for leg pain. Mean ODI change from baseline to 6 weeks post-op (–17) was almost doubled by 12 months (–32). Fusion rates at 12-months are high (98%). No device-related serious adverse events have occurred. Conclusion: 12-month outcomes demonstrated excellent patient compliance and positive outcomes for pain, function, fusion, and device safety. Clinical improvements were observed by 6-weeks post-op and appear durable up to 1 year later. A novel mesh interbody device may provide an alternative means of interbody fusion that reduces connective tissue disruption. Level of Evidence: 3 Abstract : A prospective multicenter investigational device trial is underway to evaluate the safety and effectiveness of a novel conformable mesh interbody fusion device in subjects with degenerative disc disease. Twelve-month outcomes are reported, with results showing positive outcomes for pain, function, fusion, and device safety.